Penguatan Implementasi Kurikulum Merdeka di SD Swasta As Ad Kota Jambi Melalui Bimtek Model In-On-In - A A Musyaffa; Siti Asiah; Rapiko Rapiko; Siti Ubaidah; Umil Muhsinin (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2023)
The implementation of the Independent Curriculum (IKM) rolled out by the government has caused quite a lot of confusion in the school/madrasah environment, especially for teachers. The aim of this community service research is to increase understanding and mastery of IKM for teachers and principals of SD As Ad Jambi City. The method used is an in-on-in learning model with technical guidance (bimtek) which is carried out involving multi-stakeholders. The results of the service are: (1) Bimtek is able to strengthen a number of deadlocks in IKM, so that the stuttering and worries that arise are able to turn into increased understanding and mastery of IKM, KOSP, and MA with a rate of change from 6.7 to 8.7 (2) Bimtek even able to present a solution to improve the quality of education related to the preparation of KOSP and MA, (3) technical guidance shows a significant increase in understanding and mastery of IKM, KOSP and MA, and (4) the implementation of IKM technical guidance turns out to have a positive influence on the performance of the collaborating parties. The recommendation is that the in-on-in model by collaborating with a number of schools/madrasahs, universities (PT), and other institutions is worth continuing to implement to increase understanding and mastery of SMEs, as well as to improve the performance of the parties.